O uso de dados multissectoriais para ajudar a planificação das actividades do Programa de Alimentação Escolar em Moçambique - Cunguara, Benedito; Smart, Jenny; Murphy, Cristina; Massingue, Jaquelino; Menezes, Maria Fátima (International Food Policy Research Institute, 2016)
The multisectoral nature of the National School Feeding Program in Mozambique (PRONAE) calls for the need to base investment priorities on reliable information encompassing varying dimensions including poverty, access to food, educational performance, nutritional status, potential and productive achievement, and consumption habits. Mozambique has statistical data from various sectors of the economy, and its consolidation has been lacking into one single database integrated with selected indicators of education, nutrition, poverty, health and agriculture. The aim of this paper is to promote the use of a newly constructed multisectoral database as a mechanism for integrating statistical data from different sectors of the country to provide, at ministry of Education (MINEDH) decision-making levels, a tool for multisectoral planning, analysis and evaluation of PRONAE results. Integrated analysis of sectoral outcomes across different regions of the country, from the perspective of PRONAE's potential contribution, creates the possibility for results-based policy-making. This includes setting priorities and targets in PRONAE action planning, adjusted to the existing context in the region where it is implemented. The multisectoral database enables viewing and comparing various indicators over time. This paper presents numerous examples of cross-referencing between the sectors of agriculture, health, nutrition and poverty indicators. The multisectoral database must be continuously updated as more recent data become available. While allowing for the cross-referencing of several indicators, there are other relevant indicators that current data collection systems do not incorporate. An additional fact sheet has been developed to include relevant issues to PRONAE which currently has data. Incorporating this one-page form into the current MINEDH data collection system will have enormous advantages in the process of monitoring and planning PRONAE activities.